Low cost and efficient alloy electrocatalysts for CO2 reduction to formate. (July 2019) - Rasul, Shahid; Pugnant, Adrien; Xiang, Hang; Fontmorin, Jean-Marie; Yu, Eileen H.
Graphical abstract: Highlights: Low cost Sn-Pb-Sb alloy converts CO2 efficiently to formate with 91% Faradaic efficiency. Sb in Sn rich alloy improved the conductivity and enhanced the eCO2 R activity. Enhanced eCO2 R activity is attributed to the synergistic metal/metal oxide effects. Abstract: Oxide-derived (OD) Sn and Sn−Pb−Sb composite electrocatalysts were prepared by electrochemical oxidation treatment at various potentials for electrochemical reduction of CO2 (eCO2 R) for formate (HCOO − ) production. The morphology, elemental mapping, phase identification, surface characteristics and electrochemical performance of the electrocatalysts were probed systematically. The surface of OD-Sn and OD-Sn-Pb-Sb shows polycrystalline electrodes with porous morphology and XPS results confirm the formation of composite metal/metal oxide surface related to Sn, Pb and Sb. The EDX mapping analysis shows two distant regions of Pb and Sn rich areas in the alloy. The electrochemical results demonstrate that pristine Sn electrodes show higher CO2 Faradaic Efficiency (FE) to formate compared to pristine Sn-Pb-Sb alloy electrode (80% vs. 66%) at −1.4 V vs. RHE. Upon oxidation treatment of pristine Sn at 4 V, the FEHCOO− improves to 84% at the expense of decreased current density. On the contrary, upon oxidation treatment of Sn-Pb-Sb alloy at 5 V, the FEHCOO− improved remarkably from 68% to 91% without any reduction in current density. The improved eCO2 R performance of OD-Sn and OD-Sn-Pb-Sb electrodes relative to their pristine electrodes could be attributed to the presence of composite metal/metal oxide structure which leads to local geometric and electronic structural changes.